Proteome-wide forced interactions reveal a functional map of cell-cycle phospho-regulation in S. cerevisiae - Cinzia Klemm; Guðjón Ólafsson; Henry Richard Wood; Caitlin Mellor; Nicolae Radu Zabet; Peter Harold Thorpe (Nucleus)
Dynamic protein phosphorylation and dephosphorylation play an essential role in cell cycle progression. Kinases and phosphatases are generally highly conserved across eukaryotes, underlining their importance for post-translational regulation of substrate proteins. In recent years, advances in phospho-proteomics have shed light on protein phosphorylation dynamics throughout the cell cycle, and ongoing progress in bioinformatics has significantly improved annotation of specific phosphorylation events to a given kinase. However, the functional impact of individual phosphorylation events on cell cycle progression is often unclear. To address this question, we used the Synthetic Physical Interactions (SPI) method, which enables the systematic recruitment of phospho-regulators to most yeast proteins. Using this method, we identified several putative novel targets involved in chromosome segregation and cytokinesis. The SPI method monitors cell growth and, therefore, serves as a tool to determine the impact of protein phosphorylation on cell cycle progression.